Fazendo vídeos no Colégio Ottília: tecnologia e arte como ação coletiva - Santos, Júlio César dos (2008)
This research deals with the practice of making videos at the Colégio Estadual Professora Ottília Homero da Silva, in Pinhais city, in the metropolitan region of Curitiba, differentiating what you can see from the comparison between two different genres: one, a experimental video-fiction, another, a institutional video-documentary. It addresses the production of videos at a public school, based on studies of culture and art and technology as a collective action, with emphasis on the teaching-learning processes. This research study focuses on the practice of making videos by a group of students at a public school, with the goal of finding some evidence of the implications generated by such practice as a symbolic construction and disruption of daily life imposed by certain situations, as a complex act cultural and process. Why do these people make videos over there? How this practice occurs in theses circumstances? How we give this process of building cultural symbolic? The evidence founded included the search for social integration, and extension of critical reflection, when people involved in the practice began to question their positions in the construction of their identities.